The law (and politics) of safe injection facilities in the United States. - Beletsky, Leo; Davis, Corey S; Anderson, Evan; Burris, Scott (American journal of public health, 2008)
Safe injection facilities (SIFs) have shown promise in reducing harms and social costs associated with injection drug use. Favorable evaluations elsewhere have raised the issue of their implementation in the United States. Recognizing that laws shape health interventions targeting drug users, we analyzed the legal environment for publicly authorized SIFs in the United States. Although states and some municipalities have the power to authorize SIFs under state law, federal authorities could still interfere with these facilities under the Controlled Substances Act. A state- or locally-authorized SIF could proceed free of legal uncertainty only if federal authorities explicitly authorized it or decided not to interfere. Given legal uncertainty, and the similar experience with syringe exchange programs, we recommend a process of sustained health research, strategic advocacy, and political deliberation.
Keywords: Drug and Narcotic Control; Health Policy; Humans; Local Government; Needle-Exchange Programs; Policy Making; Politics; State Government; Substance Abuse, Intravenous; United States